Using mHealth for the management of hypertension in UK primary care: an embedded qualitative study of the TASMINH4 randomised controlled trial - Grant, S; Hodgkinson, J; Schwartz, C; Bradburn, P; Franssen, M; Hobbs, FDR; Jowett, S; McManus, RJ; Greenfield, S (Royal College of General Practitioners, 2019)
BACKGROUND:Self-monitoring of blood pressure is common but how telemonitoring with a mobile healthcare (mHealth) solution in the management of hypertension can be implemented by patients and healthcare professionals (HCPs) is currently unclear. AIM:Evaluation of facilitators and barriers to self- and telemonitoring interventions for hypertension within the Telemonitoring and Self-monitoring in Hypertension (TASMINH4) trial. DESIGN AND SETTING:An embedded process evaluation of the TASMINH4 randomised controlled trial (RCT), in the West Midlands, in UK primary care, conducted between March 2015 and September 2016. METHOD:A total of 40 participants comprising 23 patients were randomised to one of two arms: mHealth (self-monitoring by free text/short message service [SMS]) and self-monitoring without mHealth (self-monitoring using paper diaries). There were also15 healthcare professionals (HCPs) and two patient caregivers. RESULTS:Four key implementation priority areas concerned: acceptability of self- and telemonitoring to patients and HCPs; managing data; communication; and integrating self-monitoring into hypertension management (structured care). Structured home monitoring engaged and empowered patients to self-monitor regardless of the use of mHealth, whereas telemonitoring potentially facilitated more rapid communication between HCPs and patients. Paper-based recording integrated better into current workflows but required additional staff input. CONCLUSION:Although telemonitoring by mHealth facilitates easier communication and convenience, the realities of current UK general practice meant that a paper-based approach to self-monitoring could be integrated into existing workflows with greater ease. Self-monitoring should be offered to all patients with hypertension. Telemonitoring appears to give additional benefits to practices over and above self-monitoring but both need to be offered to ensure generalisability.